Determinants of modern contraceptive preference among mothers (15-49 years) in central zone, Tigray region, Ethiopia; qualitative study finding - Gebremedhin, Merhawi; Belachew, Ayele; Desta, Demeke (International Journal of Medicine, 2017)
Contraceptive method choice is a fundamental indicator of quality of care in a family planning program. Contraceptive choice is one component of quality in family planning and offering minimum of three modern methods of contraceptives is a critical indicator. One-third of developing countries have many skewed method mixes, which is a risky for discontinuation, contraceptive dissatisfaction and unintended pregnancy. In Ethiopia, the prevalence of contraceptive is highly skewed, 76% for injectable. Therefore, the purpose of qualitative study was to assess determinants of modern contraceptive preference among reproductive age (15-49 years) in Central Zone of Tigray.Methodology: the study was conducted in the central zone of Tigray and community, and facility based qualitative cross-sectional study was applied. Six focus group discussion entails of reproductive age mothers and 15 In-depth Interview with health workers constitutes the sample. Data was first transcribed and then translated into English language. Open code software was applied to analyze data and data was coded segment by segment then categorized using thematic analysis to give meaning.Result: community’s awareness and acceptance to use modern contraceptives have improved from time to time. Contraceptive preference is determined by community acceptance, health care system problem, individual context and socio-cultural problem. For majority of respondents, preference to long acting contraceptive is mainly influenced by husband.Conclusion: currently, women are preferring short-acting contraceptive preferably injectable than long acting.Implanon is preferred next to injectable. A strong information, education and communication that address all portions of the population and able to change the community’s attitude should do at the grass root level.